Development of a 3D Virtual Reality Tour Media for the Siak Sri Indrapura Palace Based on the Theasys Application as a Source for Learning Local History - Refli Surya Barkara; Chandra Perwira Negara; M. Afrillyan Dwi Syahputra; Roza Sri Susanti (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The Siak Sri Indrapura Palace is a local historical heritage site with high historical and cultural value. However, a direct visit to this historical site requires time, effort, and expense. Therefore, innovative learning media are needed to bring the palace's authentic atmosphere into the classroom. Teasys is a web-based platform used to create interactive virtual reality tours. Through Teasys, users can upload photos from a 360° camera and then combine them into a virtual reality tour that appears to be directly on site. The purpose of this study was to develop a virtual reality tour media for the Siak Sri Indrapura Palace based on Teasys. This study used a Research and Development (R&D) approach to design and evaluate the effectiveness of the designed product. The development model used was the waterfall model, which includes the needs analysis stage, the media and content design stage, the product design stage, and the testing stage. The results of this study indicate that the 3D virtual reality tour media meets the adequacy standards and can be applied as a learning medium. In addition, student responses to the media showed very positive reactions.